Control of a high performance fighter aircraft by using H(infinity) theory and neural-fuzzy concepts - Zhang, Wei Qiang (2009)
This thesis provides background, theory, and examples for a high performance fighter aircraft (a modified model of F-16) control design. There are mainly three parts in this thesis. The first part presents the development of a software package for flight simulation of a high performance fighter aircraft (a modified model of F-16). The package is developed using MATLAB\SIMULINK. It consists of one SIMULINK model for simulation, one SIMULINK model for trimming/linearization and some essential functions. In this part, an overview of aircraft equations of motion is demonstrated to provide a basic understanding of flight dynamics. The fully nonlinear aircraft model is used with the six-degree-of-freedom (6-DOF) equations of motion. Some additional nonlinear aircraft dynamics such as actuator saturation, auto-scheduled leading-edge flaps and engine model are also included. C MEX-files are programmed to compute aero-dynamic coefficients and engine thrust. This makes the software package more effective and efficient in flight simulation and flight dynamic analysis. The package is also a reliable and flexible tool for checking control design methodology in the next two parts.